A theoretical framework and questionnaire for wonder-full education. Issue 3 (4th May 2022) - Conijn, Judith M.; Rietdijk, Willeke; Broekhof, Evelien; Andre, Lucija; Schinkel, Anders
ABSTRACT: Many recent studies emphasize the fundamental importance of stimulating wonder in education, for example, to increase children's intrinsic motivation to learn and their emotional engagement with the lesson contents. Our study advances the research regarding wonder in education in three different ways. First, we present a theoretical framework to identify eight teaching strategies and three school policy dimensions relevant for teachers and schools to stimulate wonder in children. Second, based on this framework, we developed the multidimensional Wonder-full Education questionnaire (WEQ). The WEQ is completed by teachers and principals to quantitatively assess the degree to which primary schools and their teachers provide a wonder-stimulating environment. Third, using comprehensive psychometric analyses of the data of N = 220 teachers and N = 91 principals from 182 Dutch schools, we investigated the dimensionality, reliability and validity of the WEQ. The dimensionality analyses identified two primary dimensions of teaching strategies and confirmed the three-dimensional structure of a school policy for stimulating wonder. Overall, the results suggest that the WEQ has satisfactory psychometric properties. We conclude that the new framework and questionnaire allow research regarding wonder in education to be extended from mainly theoretical work to empirical research that can also advance educational practice.